Rain forest - Hughes, Carol; Hughes, David; Kane, Dennis B.; Skinner, Thomas (The Society, 1983)
Showcases the rare beauty and rich variety of plant and animal life found in a Costa Rican rain forest. Also examines the impact of man's exploitation of the rain forest on this fragile ecosystem.